The Sufficient and Necessary Conditions for the Poisson Distribution Series to Be in Some Subclasses of Analytic Functions - Abdel Moneim Y. Lashin; Abeer O. Badghaish; Amani Z. Bajamal (Journal of Function Spaces)
In this paper, we introduce new subclasses of analytic functions in the open unit disc. Furthermore, the necessary and sufficient conditions for the Poisson distribution series to be in these new subclasses are found.